PH modulating agar dressing for chronic wounds. Issue 4 (2nd October 2022) - Tyeb, Suhela; Kumar, Nitesh; B, Gorbel; Kumar, Ashok; Verma, Vivek
ABSTRACT: Microenvironment of majority chronic wounds exhibits pH in the range of 7.5 to 8.5, leading to poor healing prognosis. The elevated pH adds to dysregulation of healing cascade by creating hypoxia, elevating matrix metalloproteinase (MMP) activity and chances of infection. The current work focuses on fabrication of pH regulating agar-citric acid bi-layer dressing for effective management of chronic wounds. The desired pH in the range of 6 to 7 was achieved by unidirectional release of citric acid through bi-layer arrangement of agar-citric acid films in contact with wound simulating fluid of pH 8.5. At lower pH (6.5), both MMP 9 and MMP 2 degraded lesser gelatin (0.11 µg/mg ± 0.003 µg/mg) as compared to higher pH (8.5) value (0.18 µg/mg ± 0.004 µg/mg). The dressing also exhibited bacteriostatic effect on Staphylococcus aureus and Pseudomonas aeruginosa bacteria cultured in-vitro. The bilayer dressing exhibited an average tensile strength of 27 MPa ± 2.5 MPa along with 52 ± 5% elongation at break. The percentage swelling and water vapor transmission rate of dressing was 112% ± 20% and 2156 g/m 2 /day ± 128 g/m 2 /day respectively.